Cover. Issue 2 (7th February 2020) - Akler, Gidon; Birch, Ashley H.; Schreiber‐Agus, Nicole; Cai, Xiaoqiang; Cai, Guiqing; Shi, Lisong; Yu, Chunli; Larmore, Anastasia M.; Mendiratta‐Vij, Geetu; Elkhoury, Lama; Dillon, Mitchell W.; Zhu, Jun; et al.
Abstract : The cover image is based on the Original Article Lessons learned from expanded reproductive carrier screening in self‐reported Ashkenazi, Sephardi, and Mizrahi Jewish patients by Gidon Akler et al., https://doi.org/10.1002/mgg3.1053 .